Effects of a quality improvement collaborative on the outcome of care of patients with HIV infection: the EQHIV study. - Landon, Bruce E; Wilson, Ira B; McInnes, Keith; Landrum, Mary Beth; Hirschhorn, Lisa; Marsden, Peter V; Gustafson, David; Cleary, Paul D (Annals of internal medicine, 2004)
Multi-institution collaborative quality improvement programs are a well-established and broadly applicable quality improvement strategy, but there is little systematic assessment their effectiveness.
Keywords: AIDS-Related Opportunistic Infections; Data Collection; HIV Infections; Humans; Mass Screening; Program Evaluation; Prospective Studies; Quality Assurance, Health Care; Quality Indicators, Health Care; Viral Load